Manajemen Skala Suara Dalam Menanamkan Kedisiplinan Anak Usia Dini - Lulu Febriyanti; Hajeni Hajeni; Rahmatia Rahmatia (Universitas Pahlawan Tuanku Tambusai, 2022)
Sound scale management in instilling discipline in early childhood is very important because it can help children develop disciplined character. This study used a descriptive method with a qualitative approach. The informants of this study were the principal and 5 accompanying teachers. Data collection techniques in this study used interview techniques, observation techniques, and documentation techniques. Based on the results of the study it was found that there were 3 stages in sound scale management in instilling discipline in early childhood, namely sound scale planning, sound scale implementation and sound scale evaluation. The planning of the sound scale was planned by the guidance counselor and then a meeting was held with the teacher and socialization to the parents of students, the implementation of the sound scale had 4 scales, scale 0, scale 1, scale 2, scale 3, scale 4. Scale 0 when the call to prayer is echoed, scale 1 talking with someone, scale 2 expressing opinions/speaking in small groups (3-20 people), scale 3 talking/playing in open spaces in large groups (20-50 people), scale 4 emergency: fire. Sound scale evaluation has advantages and disadvantages. The teacher has made a plan, implemented and evaluated which is able to develop a child's discipline attitude through habituation activities so that it can be concluded that the planning, implementation and evaluation carried out to instill discipline in children is in accordance with what is expected by the teacher.